Eksperimen Fotografi Interior Pada Hotel The House Tour di Bandung - Sandy Dwi Putra; Kankan Kasmana (ARTic, 2020)
The rapid advancement of information and communication technology influences the growth of creative industries such as firms in the fields of architecture, real estate and interior. The firm uses the advantages of information and communication technology, namely the internet and social media to conduct marketing. The use of social media as a marketing strategy of real estate and interior firms today is increasingly used as a promotional medium. The use of photos especially for interior promotion requires good photography techniques, has the power to stir consumer perception of interior services. This research aims to conduct photography experiments on the interior of The House Tour Hotel, designed by an architecture firm called Be Good Design Architect, this experiment was conducted to find out the techniques of photography in photographing the interior. The method used is photography experimentation using photography techniques based on literature and photographic methods from interviews with professional photographer Mario Wibowo. The result of this experiment is interior photo taken from the bedroom room of The House Tour Hotel.